A New Ethylene-Responsive Factor CaPTI1 Gene of Pepper (Capsicum annuum L.) Involved in the Regulation of Defense Response to Phytophthora capsici - Jin, Jing-Hao; Zhang, Huai-Xia; Tan, Jun-Yi; Yan, Ming-Jia; Li, Da-Wei; Khan, Abid; Gong, Zhen-Hui (Frontiers in Plant Science, 2016)
Ethylene-responsive factors (ERF) are usually considered to play diverse roles in plant response to biotic and abiotic stresses. In this study, an ERF gene CaPTI1 was isolated from pepper transcriptome database. CaPTI1 contains an open reading frame (ORF) of 543bp, which encodes a putative polypeptide of 180 amino acids with a theoretical molecular weight of 20.30 kDa. Results of expression profile showed that CaPTI1 had a highest expression level in roots and this gene could not only response to the infection of Phytophthora capsici and the stresses of cold and drought, but also be induced by the signaling molecule (salicylic acid (SA), Methyl Jasmonate (MeJA), Ethephon (ETH) and hydogen peroxide (H2O2)). Furthermore, virus-induce gene silencing (VIGS) of CaPTI1 in pepper weakened the defense response significantly by reducing the expression of defense related genes CaPR1, CaDEF1 and CaSAR82 and also the root activity. These results suggested that CaPTI1 is involved in the regulation of defense response to P. capsici in pepper.